Child sacrifice in Uganda: adequacy of existing legal provision - Bogere, Philippa (2014)
This article highlights the various incidences of child sacrifice in the country and the legislation in place. It also argues that despite the legislation in place, the incidence of child sacrifice still thrives in Uganda's society due to various factors including failure to enforce the laws in place. The first part examines the situation of child sacrifice currently and the major causes of the practice. The paper examines the legal framework and gaps in the current laws for fighting violence against children. It also contains a brief discussion on how effective the domestic laws are in the current context.